HOW TO IMPROVE WRITING SKILLS IN ENGLISH LANGUAGE - Sefrina Anastasya Simbolon; Tiarnita Maria Sarjani br. Siregar; Azizi Riona; Gloria Pasca Simarmata; Miranda Simangunsong; Sherin Aurelya; Zahra Tusyita Siregar (Interdisciplinary Journal of Advanced Research and Innovation, 2023)
Writing is one of the most important skills that learners of English as a second language must master, especially for students and working professionals. Unlike speaking practice, when you write, you leave a lasting record of your language. This is because it reinforces the grammatical structures and terminology that educators seek to teach their students. Therefore, it is necessary to improve writing skills. This article discusses various effective strategies and techniques to improve writing skills in English. The method used in this journal is library research, collecting data by finding sources and reconstructing them from various sources such as books, and existing research. This article discusses the importance of strong writing skills in today's globalized world and offers practical advice for individuals who want to improve their proficiency. By reading this article, readers can develop their English writing skills and gain the confidence needed to communicate effectively in academic and professional contexts.